METHODS OF CONDUCTING PHYSICAL EXERCISES IN CHILDREN (Web of Teachers: Inderscience Research, 2026)
Physical activity plays a crucial role in the healthy development of children, contributing to their physical, mental, and social well-being. This study explores various methods of implementing physical exercises among children, emphasizing age-appropriate approaches, safety considerations, and the role of structured versus unstructured activities. The findings highlight the importance of combining playful activities with guided exercises to enhance motor skills, coordination, and overall health. Recommendations are provided for educators, parents, and policymakers to promote effective physical activity routines in children.